The Role of Cosmetological Procedures and Hand Care Techniques in the Pathogenesis of Onycholisis - Iliuk, Tetiana (Global Prosperity, 2025)
Onycholysis is one of the most common symptoms of nail damage, and recent years have been characterized by a noticeable increase in its association with cosmetic procedures, in particular the intensive use of gel and acrylic coatings. The aim of the study was to determine the role of cosmetic procedures and hand care techniques in the pathogenesis of onycholysis. Materials and methods. During the work, an analysis of modern scientific publications devoted to the study of the pathogenesis of onycholysis was conducted. The search for works was carried out in scientometric databases "Web of Science", "Scopus", "PubMed", "Google Scholar". Methods of theoretical generalization, analysis and synthesis of results were used. Results. During the work, it was established that the main factors in the development of onycholysis are trauma to the nail during manicure, the use of chemically aggressive primers, frequent removal of coatings, as well as contact with allergens. The article notes that an important role is also played by incorrect manicure technique, prolonged wearing of false nails without rest, violation of the barrier function of the cuticle, ignoring protective equipment when in contact with moisture and detergents. Clinical variants of onycholysis are described: traumatic, allergic, infectious, photoinduced. It was found that in most cases cosmetically induced onycholysis has a mixed nature. This is a combination of mechanical and chemical damage with a possible allergic component. The work emphasizes the importance of differentiating such conditions from fungal lesions and nail psoriasis. The need to develop standards for safe manicures, introduce hypoallergenic technologies, and raise awareness among nail technicians and clients about preventing nail damage was emphasized. Conclusions. Cosmetic procedures and hand care techniques affect the development of onycholysis. To prevent onycholysis, it is necessary to adhere to gentle manicure techniques, take breaks in wearing artificial coatings, protect hands from excessive moisture and chemicals, and consult a dermatologist in a timely manner if signs of peeling appear. In addition, it requires standardization of the safe use of nail cosmetics and rehabilitation of nails after injuries, which determines the directions of further research in this area.